1893 Del. Laws 263 - (:unkn) unknown (My University, 1893)
An Act for the Protection of Fish and Game In and on the Waters of the Delaware Bay and River, and The Streams, Tributary Thereto, Within the Limits of this State, ch. 216, § 1: Prohibited non-Delaware citizens from hunting, shooting, or killing any geese, ducks, fowls, birds, or other kind whatever. Violators forfeit the boat, vessel, and/or gun used to violate the act. Violators also shall pay a fine of two hundred dollars for each offense.
Keywords: HUNTING REGULATION